"YES it's the Perfect Time to Quit": Fueling Tobacco Cessation in India during COVID-19 Pandemic. (September 2020) - Grover, Shekhar; Mohanty, Vikrant; Jain, Swati; Anand, Tanu; Aghi, Mira B
Entire world is battling the Novel Coronavirus Disease (COVID-19) pandemic. India too, has undertaken stringent containment measures to combat this disease. The country is in a state of national lockdown, which has inadvertently led more than a quarter of the Indian population to not use tobacco. This paper discusses the opportunity that surfaces with unavailability of tobacco products, and advocates the need for escalation of tobacco cessation services as well as strategic management of stress to stay tobacco-free.